North east and north west: An italian regional competition for international success - Giorgio Dominese (European Regional Science Association (ERSA), 2001)
The paper intends to highlight the development and the competitive standing of two Italian regions, the North East and the North West. In the past 30 years, the average GNP growth registered by the North East, comprising in its enlarged” version (North East 2) Veneto, Friuli Venezia Giulia, Trentino-South Tyrol (North East 1) and Emilia Romagna, was not only above the national average but also above the results recorded by the North West comprising in its “enlarged” version (North West 2) Piedmont, Valle d'Aosta, Liguria (North West 1) and Lombardy. During the 90's, the North East 2 area posted an average GNP growth of 2% against an average of 1,1%25 of the North West 2 and of 1,3% registered by Italy as a whole. This development was due to the presence of small and medium-sized highly internazionalized enterprises. The dynamic trend was led mainly by exports, especially in the North East 2. After the lira devaluation in 1992, the share of exports was particularly high also on the national level. Between 1996 and 1999 the North East's exports increased by 12,9% whereas at the same time the national growth rate was only 7,7% and the North West 2 registered a growth of 1,3% due to the essential contribution of Lombardy. In the first six months of 2000, exports have been particularly dynamic both in the North East 2 (+13%) and the North West 2 area (+19%). The internationalization of the enterprises of the North East 2, which is very high if considered in terms of share of foreign trade on turnover, shows however serious weak spots if examined in terms of direct investments in other countries. From 1996 to 1999, direct investments of the North West 2 amounted to only 89.000 billion lire, which corresponds to nearly one third of the national volume. In the North East 2 this figure was even more modest reaching only 13.800 billion lire (11,3% of the national volume). At the end of 1999, in the North West 2 area more than 1.263.000 enterprises were operating, corresponding to 26,5% of the total number of Italian enterprises. In the North East 2 area approximately 1.048.000 enterprises (22% of the total of national enterprises) are located. In the period 1997-1999 the number of enterprises in the North West 2 recorded a slight increase (+1%) whereas in the North East 2 their number remained more or less the same. Diversification of the production, diffusion in the territory and the positive employment structure have always been distinctive elements of the North West and the North East. The national unemployment rate of about 10,8% (which registered a slight downward trend as compared to 11,4% in 1999) falls to 5,4% in the North West and to 4,3% in the North East. The predominance of small enterprises, very often of an artisan type, characterized by a low level of capital resources, is the basis for a strong relation with the local credit system and only a limited interest in engagements in the capital markets. It does not surprise therefore that in the first quarter of 2000 in the North East the assets have grown by nearly 51% and in the North West by 42% as compared to the national level of 29,5%. The paper concludes with a comparative analysis between the two German regions Bavaria and Baden-Württemberg, the Spanish region Catalonia and the Italian North East and North West, based on the flows of foreign trade and foreign direct investments in the last three years. *Giorgio Dominese, expert and researcher of international economy is Director of Csne-North East Study Center of Venice and of Isdee-Institute for the Study and Documentaton of the European Community and Eastern Europe. Recently he has been appointed Program Director of ICETS-International Center for Transition Studies of the University Luiss-Guido Carli of Rome and the University of Trieste. He is also member of the Business Advisory Council of SECI-Southeast European Cooperative Initiative.
Keywords: 330